Modulation of Plant MicroRNA Expression: Its Potential Usability in Wheat (Triticum aestivum L.) Improvement - Lopos, Louie C.; Panthi, Urbashi; Kovalchuk, Igor; Bilichak, Andriy (Current Genomics, 2023)
Wheat, a crucial crop for the pursuit of food security, is faced with a plateauing yield projected to fall short of meeting the demands of the exponentially increasing human population. To raise global wheat productivity levels, strong efforts must be made to overcome the problems of (1) climate change-induced heat and drought stress and (2) the genotype-dependent amenability of wheat to tissue culture, which limits the success of recovering genetically engineered plants, especially in elite cultivars. Unfortunately, the mainstream approach of genetically engineering plant protein-coding genes may not be effective in solving these problems as it is difficult to map, annotate, functionally verify, and modulate all existing homeologs and paralogs within wheat's large, complex, allohexaploid genome. Additionally, the quantitative, multi-genic nature of most agronomically important traits furthers the complications faced by this approach. miRNAs are small, noncoding RNAs (sncRNAs) that repress gene expression at the post-transcriptional level, regulating various aspects of plant growth and development. They are gaining popularity as alternative targets of genetic engineering efforts for crop improvement due to their (1) highly conserved nature, which facilitates reasonable prediction of their gene targets and phenotypic effects under different expression levels, and (2) the capacity to target multiple genes simultaneously, making them suitable for enhancing complex and multigenic agronomic traits. In this mini-review, we will discuss the biogenesis, manipulation, and potential applications of plant miRNAs in improving wheat's yield, somatic embryogenesis, thermotolerance, and drought-tolerance in response to the problems of plateauing yield, genotype-dependent amenability to tissue culture, and susceptibility to climate change-induced heat and drought stress.
Keywords: somatic embryogenesis